Add-on mirtazapine improves orgasmic functioning in patients with schizophrenia treated with first-generation antipsychotics. (2nd January 2017) - Terevnikov, Viacheslav; Stenberg, Jan-Henry; Tiihonen, Jari; Burkin, Mark; Joffe, Grigori
Abstract: Aim: Sexual dysfunction, common in schizophrenia, may be further exaggerated by antipsychotics, especially those of First Generation (FGAs), and antidepressants, such as Selective Serotonin Reuptake Inhibitors (SSRs). Mirtazapine, an antidepressant characterized by its different action mechanism compared with that of the majority of other antidepressants, may improve SSRI-induced sexual dysfunction in patients with depression. It is unknown, however, whether mirtazapine improves sexual functioning in schizophrenia. Methods: This study randomly assigned FGA-treated patients with schizophrenia to receive either an add-on mirtazapine ( n  = 20) or a placebo ( n  = 19) for 6 weeks. Sexual functioning was prospectively measured using five relevant items from the Udvalg for Kliniske Undersogelser side-effect rating scale (UKU-SERS). Results : Orgasmic function improved with statistical significance in the mirtazapine group ( p  = .03), with no changes in any other sexual functions in either group. Conclusion: Add-on mirtazapine appears to relieve orgasmic dysfunction in FGA-treated patients with schizophrenia.